ASSESSING THE IMPACTS OF COVID-19 ON MEGA SPORTING EVENTS: A CASE OF THE 2022 FIFA WORLD CUP IN QATAR - Al-Dosari, Khalifa Nasser K A (Global Journal of Health Sciences, 2020)
Purpose: The study sought to assess the impacts of covid-19 to the sporting industry, focusing on mega sporting events, a case of the 2022 FIFA World Cup in Qatar. The research focused on analysing the different stakeholders involved in these sporting events. Methodology: The research adopted a cross-sectional research study with a sample size of 60 respondents, including FIFA and government officials, officials in the professional sports ecosystem, such as the players, broadcasters, owners of sports businesses, and fans. The study used both purposive and random sampling techniques to sample respondents from different categories. Insofar as data on health impacts of Covid-19 were concerned, the researcher adopted purposive sampling to select a few athletes and physicians from the pilot study. Also, the researcher purposively sampled FIFA and government officials to provide data on the economic and financial implications of Covid-19. However, respondents insofar as data on the social effects of Covid-19 was concerned were randomly sampled from individuals within Qatari population who were considered football fans. Data were collected by the use of online questionnaires sent to the respondents electronically. The data obtained was categorised in the form of economic impacts, social impacts, financial impacts, and health impacts of covid-19. The quantitative data collected was analysed through the comprehensive quantitative analysis and descriptive statistics by use of frequencies and percentages. The sample data was also subjected through a Chi-square test of significance. Posteriori tests were also conducted where necessary, with Bonferroni adjustments. The findings of the study were presented using tables and charts. Findings: The research found out significant economic, social, financial, and health impacts of Covid-19 on mega sporting events. Regarding financial impacts, the results indicated that Covid-19 has adversely affected financial planning as well as budgeting of mega sporting events. Regarding the economic impacts, the findings revealed that Covid-19 has caused high unemployment for people working within the sporting ecosystem as well as players, leading to adverse effects of their living standards due to high cost of living. Also, the study found that most people feared attending the 2022 FWC due to Covid-19 as well as interaction with tourists from countries highly infected with Covid-19., thus undermining social interactions. Moreover, the findings on the health impacts were also significant, with most respondents agreeing that they were at risk of exposure to Covid-19 and also that athletes' physical and mental health was affected due to the uncertainty in the sports industry. Unique contribution to theory, practice and policy: The study recommended that FIFA and governments should find measures to handle future pandemics to ensure the adverse impacts found out in this study are managed towards enhancing the resilience for mega sporting events during pandemics.